TINJAUAN YURIDIS MENGENAI KEKERASAN PADA PEREMPUAN DALAM KEJAHATAN CYBERCRIME - Syahrian, Mochammad Rifky; Nugroho, Widhi Cahyo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
All human actions in the current digital era are substantially supported by the internet’s presence in daily life. Nevertheless, the development of technology and the usage of the internet, among other factors, have led to the creation of cybercrime. Cybercrime demands unique handling by the police during the investigation process due to its evolution. Due to this, this study will evaluate the hectic nature of the cybercrime investigation process utilizing normative juridical research. The method is essentially the same as the criminal investigation process in general, with the exception that cyber units or special units charged with investigating cybercrime carry out the inquiry. Although the harm inflicted by cybercrime is incalculable, Indonesia’s law that deals with it expressly isn’t yet up and running. Although they cannot be used to all sorts of cybercrime crimes that exist, some provisions of the Criminal Code (KUHP) can be utilized to catch criminals connected to computers or the internet. Women are the victims of online gender-based violence (OGBV), a type of cybercrime. The need for legal protection for OGBV victims is critical. Both the trafficking law (Law No. 21/2007), the pornography law (Law No. 44/2008), which governs guidance, assistance, social recovery, as well as the physical and mental health of children who are pornography victims or perpetrators, and which also regulates restitution (Article 48), health rehabilitation, social rehabilitation, repatriation, and social reintegration, control the legal safeguards for those who experience internet aggression against women (Article 16). In light of this, how was Indonesian law addressing and protecting against women being abused through cybercrime or internet networks while this piece was being written?